THE PRINCIPLE OF PROPORTIONALITY, THE IMPLEMENTATION OF EU LAW, THE PUBLIC ADMINISTRATION. GENERAL AND PRELIMINARY ASPECTS - Oana ŞARAMET (Challenges of the Knowledge Society (CKS) Nicolae Titulescu University of Bucharest, 2019)
Fundamental principle of EU law is governed, at present, by Article 5 (4) of the EU Treaty, as well as Article 5 from the Protocol no 2 of the Lisbon Treaty, the Protocol on the application of the principle of subsidiarity and proportionality. This principle implies that the content and form of Union action shall not go beyond what is necessary to achieve objectives of the Treaties. Established constitutionally by the provisions of Article 53 (2) of the Romanian Constitution, the principle of proportionality cannot and should not be ignored in public administration, obviously. In our opinion, taken into consideration our national constitutional regulation could come off an erroneous conclusion that the proportionality concerns only the restriction of certain rights, not being necessary to govern the activity of public administration. But such an assertion cannot be supported at EU level where its action, its institutions actions and the Member States action that falls within the sphere of EU law are conditioned on the compliance with this principle. Moreover, even at national level, by the Strategy for consolidation public administration for 2014-2020, adopted by Government Decision no. 909/2014, the principle of proportionality is recognized as one of the general principles underpinning this strategy and, especially, the public administration through its activity. Also, for example, the proportionality was settled as a principle in the draft Code of Administrative Procedure, a relevant issue even if this bill did not become a law until now. In same context, after the ECJ decision in the case C-8/55 Fédération Charbonnière de Belgique v. High Authority of European Coal and Steel Community, the Court of Justice consistently recognized, in its jurisprudence, the existence and the applicability of this principle, such as is revealed by the jurisprudence of the Constitutional Court of Romania. Good governance, but also the control mechanisms developed to protect and guarantee such governance requires a Member State, such as ours, the implementation of EU law by national authorities by taken into consideration even of the principle of proportionality that will focus on the policies chosen to be applied, the administrative and judicial measures applicable, the recognized, protected and guaranteed rights.
Keywords: proportionality; principle; public administration; good administration; good governance